2021
DOI: 10.3389/fphys.2021.566023
|View full text |Cite
|
Sign up to set email alerts
|

NOS3 Polymorphisms Can Influence the Effect of Multicomponent Training on Blood Pressure, Nitrite Concentration and Physical Fitness in Prehypertensive and Hypertensive Older Adult Women

Abstract: Associations of endothelial nitric oxide synthase (NOS3) polymorphisms with hypertension and response to exercise training in prehypertensive and hypertensive older adult women remain unclear. This study used a multicomponent program (various capacities and motor skills) in the physical training intervention. It analyzed the influence of NOS3 polymorphisms [−786T > C, 894G > T (Glu298Asp), and intron 4b/a] on the response of blood pressure (BP), nitrite concentration, and physical fitness in olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This claim is confirmed by a recent systematic review with a meta-analysis, which found that the combination of both exercise modalities may significantly reduce SBP and DBP in postmenopausal women [54]. Additionally, other investigations that used the MTP in their physical exercise intervention were also in accord with our study [22,53,55], demonstrating significant reductions in blood pressure. Furthermore, similar to our study, Cornelissen et al [7] reported that reductions in SBP and DBP were attributed to cardiorespiratory improvements.…”
Section: Discussionsupporting
confidence: 89%
“…This claim is confirmed by a recent systematic review with a meta-analysis, which found that the combination of both exercise modalities may significantly reduce SBP and DBP in postmenopausal women [54]. Additionally, other investigations that used the MTP in their physical exercise intervention were also in accord with our study [22,53,55], demonstrating significant reductions in blood pressure. Furthermore, similar to our study, Cornelissen et al [7] reported that reductions in SBP and DBP were attributed to cardiorespiratory improvements.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the investigated NOS3 polymorphisms (−786T > C and 894 G > T), the studies provide inconclusive findings [ 12–15 ]. However, in a study conducted by our group [ 17 ], a distinct response to multicomponent training, lasting 90 minutes per session, was observed among groups of older women with pre-hypertension (pre-HAs) and hypertension (HAS). It was evident that improvement and response were associated with genotype, with the presence of the three variant genotypes [−786T > C: TC + CC, 894 G > T (Glu298Asp): GluAsp + AspAsp] negatively affecting the reduction of diastolic blood pressure and the increase in nitrite concentration responses, particularly in the group of older women with HAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals may exhibit different responses in BP after a period of exercise training practice [ 12–15 ]. Genetic variables, such as NOS3 polymorphisms, may be related to differences in responses to exercise training [ 12 , 13 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations